1991
DOI: 10.1128/jcm.29.9.1934-1939.1991
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing determination of high-level aminoglycoside resistance in Enterococcus faecalis

Abstract: The ability of seven methods to detect high-level gentamicin (58 strains) and streptomycin resistance (56 strains) among 107 Enterococcusfaecalis isolates was investigated at the University of Chicago Medical Center and the University of Nebraska Medical Center. Methods included a standard agar screen plate, high-content disk diffusion, Remel (Lenexa, Kans.) EF Synergy Quad plates, standard microdilution panels prepared in house, Pasco MIC Gram-Positive panels (Difco Laboratories, Detroit, Mich.), MicroScan MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
3
15
1
Order By: Relevance
“…Prolonging of incubation to 48 h had no notable effect on the inhibition zone diameters that were obtained. These findings are consistent with those of previous studies that have shown high-content disk diffusion to be a reliable method for detecting resistance in E. faecalis (9,11,13). False resistance did not occur by either the standard or Pasco microdilution methods ( Table 2).…”
Section: Notessupporting
confidence: 92%
See 3 more Smart Citations
“…Prolonging of incubation to 48 h had no notable effect on the inhibition zone diameters that were obtained. These findings are consistent with those of previous studies that have shown high-content disk diffusion to be a reliable method for detecting resistance in E. faecalis (9,11,13). False resistance did not occur by either the standard or Pasco microdilution methods ( Table 2).…”
Section: Notessupporting
confidence: 92%
“…Additionally, with swab inoculation, several resistant isolates showed weak growth in the presence of 2,000 ,tg of gentamicin per ml. As has been recommended for E. faecalis (9,14), prolonging of incubation to 48 h when weak or light growth, in comparison with the growth control, is observed at 24 h enhances resistance detection in some isolates. BHI results indicate that some of these problems might be related to the growth medium.…”
Section: Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented here also demonstrate the inadequa-cies inherent in the MicroScan and Vitek systems for the detection of enterococcal resistance to other antimicrobial agents commonly used for therapy. The problem of detecting high-level aminoglycoside resistance has been addressed previously, with the recommendation that a single-concentration agar screen plate or a high-potency disk be used in conjunction with the commercial systems (12,13,20,21,25). Similarly, the lack of sensitivity of the MicroScan panels and the lack of specificity of the Vitek cards to detect ampicillin resistance have been noted previously (12).…”
Section: Discussionmentioning
confidence: 99%